Revision of the types of the genus Rhamphomyia species (Diptera, Empididae) described by R. Frey from the collection of the Zoological Institute of Russian Academy of Sciences, St. Petersburg - Shamshev, Igor V.; Barták, Miroslav; Saigusa, Toyohei (Zootaxa, 2022)
Type material for 36 species of the genus Rhamphomyia Meigen described by R. Frey from the collection of the Zoological Institute of the Russian Academy of Sciences, St. Petersburg is discussed. Habitus photo, label data, type locality and condition of the primary type specimen are provided for 30 species. Lectotype designations are made for the following 20 species (original combinations): Rhamphomyia antennata Frey, 1915; R. (Ctenempis) chrysodactyla Frey, 1950; R. (C.) gripha Frey, 1935; R. (C.) ussuriensis Frey, 1950; R. (Dasyrhamphomyia) ornithorhampha Frey, 1950; R. (D.) pleciaeformis Frey, 1950; R. (D.) taimyrensis Frey, 1950; R. (Eorhamphomyia) basispinosa Frey, 1950; R. (E.) multisinuosa Frey, 1950; R. (E.) principalis Frey, 1950; R. (E.) setitibia Frey, 1950; R. (Megacyttarus) cymbella Frey, 1950; R. (Pararhamphomyia) barbipalpis Frey, 1950; R. (P.) mendicula Frey, 1950; R. (P.) semipellucida Frey, 1950; R. (P.) stackelbergi Frey, 1950; R. (P.) transversipyga Frey, 1950; R. (Rhamphomyia) filipjefi Frey, 1950; R. (R.) paraleucoptera Frey, 1950; R. (R.) subtibialis Frey, 1950.